2023
DOI: 10.1111/jan.15890
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of heart failure patients based on their psychological and physical symptoms and predictive analysis of cluster membership

Giulia Locatelli,
Paolo Iovino,
Alessandro Pasta
et al.

Abstract: AimPatients with heart failure experience multiple co‐occurring symptoms that lower their quality of life and increase hospitalization and mortality rates. So far, no heart failure symptom cluster study recruited patients from community settings or focused on symptoms predicting most clinical outcomes. Considering physical and psychological symptoms together allows understanding how they burden patients in different combinations. Moreover, studies predicting symptom cluster membership using variables other tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…In our study, most participants (53.2%) belonged to the cardiopulmonarydepressive symptom cluster profile, which is similar to those reported in the literature that found integrated physical and psychological symptoms in patients with HF. 11,17,27 Compared with the low-burden symptom cluster profile, it is not surprising that comorbidity was associated with membership in the high-burden and cardiopulmonarydepressive symptom cluster profiles. Notably, we found that the risk of lung disease for highburden symptom cluster profiles is about 5 times higher than that of low-burden symptom cluster profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, most participants (53.2%) belonged to the cardiopulmonarydepressive symptom cluster profile, which is similar to those reported in the literature that found integrated physical and psychological symptoms in patients with HF. 11,17,27 Compared with the low-burden symptom cluster profile, it is not surprising that comorbidity was associated with membership in the high-burden and cardiopulmonarydepressive symptom cluster profiles. Notably, we found that the risk of lung disease for highburden symptom cluster profiles is about 5 times higher than that of low-burden symptom cluster profiles.…”
Section: Discussionmentioning
confidence: 99%
“…8 Symptom profiles encompass physical and psychological (emotional) domains that may differ depending on the demographic and clinical attributes of the participants. 5,9,10 Previous studies have indicated that symptoms among adults with HF (age ≥ 18 years) recruited from hospital wards, 11 outpatient HF clinics, 9,[12][13][14][15][16] and healthcare centers, 17 occur in clusters or cluster profiles. However, these studies were conducted in specific regions, lacked national representation, and had limited generalizability due to their small sample sizes.…”
Section: Introductionmentioning
confidence: 99%